Pesticide Labeling: Precautionary Statements - Frederick M. Fishel (EDIS)
Precautionary statements found on pesticide labeling tell the user information about the toxicity, irritation, and sensitization hazards associated with the use of the pesticide. These labels also provide treatment instructions and information to reduce exposure potential. This 5-page fact sheet describes the different types of statements found on pesticide labels, as well as the instructions for personal protective equipment, and first-aid treatments. This publication also contains several reference tables for pesticide labels and their meanings. Written by Frederick M. Fishel, and published by the Agronomy Department, December 2015.